P12 Child Deaths Due to Injury in Four UK Countries: 1980 to 2010. (4th June 2013) - Hardelid, P; Davey, J; Dattani, N; Gilbert, R
Abstract : Aims: To examine trends in child deaths due to injury England, Scotland, Wales and Northern Ireland between 1980 and 2010. Methods: Data from death certificates from children who died aged 28 days to 18 years between 1980 and 2010 were obtained from the national statistics agencies in the four countries. Injury deaths, including poisoning, was defined by an external cause code (from the International Classification of Diseases) recorded as the underlying cause of death. We estimated rates of injury deaths per 100, 000 resident children by sex, age group (28 days to nine years, and 10 to 18 years), time period, country of residence and type of injury (accidental or non-accidental). Mortality rates were adjusted for reporting delay. Results: Child mortality due to injury has declined in all four countries of the UK. England consistently experienced the lowest mortality rate throughout the study period. For children aged 28 days to nine years, differences in mortality rates between England and the other three countries declined over the study period, whereas for children aged 10 to 18 years, differences in mortality rates increased. Inter-country differences were largest for boys aged 10 to 18 years with mortality rate ratios of 1.34 (95% confidence interval 1.13, 1.60) for Wales, 1.66 (1.46, 1.89) for Scotland and 1.83 (1.52, 2.21) for Northern Ireland compared to England (the baseline). The decline in mortality due to injury was accounted for by a decline in accidental deaths; no declines were observed for any age groups for non-accidental deaths, that is deaths caused by self-harm, assault or from undetermined intent. Conclusions: Whilst child deaths from injury have declined in all four UK countries, substantial differences in mortality rates remain between countries, particularly for older boys. This group stands to gain most from policy interventions to reduce deaths from injury and poisoning in children.